Pembelajaran Akhlak Berbasis Teori Keseimbangan Perilaku Moral - Nursyamsiah, Nunung (Jurnal Studi Agama dan Masyarakat, 2017)
This study examines the characteristics of teaching materials that can lead to moral feeling conflict; a classroom activity model that can reinforce moral feeling conflict, followed by a change of moral feeling until the occurrence of an imbalance of moral feeling; and the characteristics of lecture assignments that can encourage the process of internalization of character values and enable the occurrence of the values actualization in student life. The subjects of the study are Arabic Language Education students who take Tahdzibul Akhlaq course in the even semester of 2013/2014. Based on the results of interviews, observations, and documentation of students